Andrea Pozzo’s architecture treatise and its reflections in the Minas Gerais gilded sculptures - Pedrosa, Aziz José de Oliveira (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2014)
The production of gilded sculpture in Minas Gerais in the 18th century was possible due to the presence of Portuguese craftsmen who came to Brazil from different regions Portugal, searching for good opportunities of architecture and ornamentation works in the church which were built in Minas Gerais. Architects, Woodcarvers and other professionals who dedicated to arts and crafts were responsible to produce the gilded sculpture, needed ornaments to let the churches able to shelter the faith of a population in the middle of formation. These same men were also responsible to bring artistic innovations from the Baroque Europe inside the Minas Gerais’ churches and use them according to the local conditions which were different from the European context. However, it’s not very known how the architecture and ornamentation patterns spread in the Minas Gerais County, but the discovery of José Coelho de Noronha’s small library opens new possibilities to debate this subject end suggests that architecture treatises were very used there in the 18th century. This article talks over the possibility of some of José de Coelho Noronha’s books could be Andrea Pozzo’s architecture treatise, which were widely accepted and known in European Artistic world and certainly reflected in the Minas Gerais County.